Leaf-litter spider diversity in the tropical forest of northern Vietnam in relation to regional condition and habitat structure - Sac, Pham Dinh; Thu, Tran Thi Anh; Shuqiang, Li (Academia Journal of Biology, 2012)
A survey of leaf-litter spiders was carried out in April 2008 and March 2009 at three National Parks in Northern Vietnam, such as, Cuc Phuong National Park (CPNP, red river delta tropical monsoon climate), Tam Dao National Park (TDNP, high mountain tropical monsoon climate) and Cat Ba National Park (CBNP, maritime climate). Four types of habitat chosen at each region are natural forest and disturbed forest (have multi-layer vegetation structure), shrub-land and acacia plantation (have simple-layer vegetation structure). The spiders were sampled by leaf-litter sieving. A total of 8787 adults (251 species, 33 families) from three regions were found, including 2846 adults (142 species) in CPNP, 3184 (137) in TDNP and 2757 (124) in CBNP. Sheet-line weavers and cursorial hunters were the dominant guilds at study area. The MDS plots and ANOSIM analyses used to compare the diversity of leaf-litter spiders between regions and between habitats. The species composition of three regions was significantly different between region with maritime climate conditon (CBNP) and the rest regions. The abundance, species richness and diversity index were higher in habitats that multi-layer vegetation structure. The species and guild composition were considerably different between two types of habitat. The relationships between diversity of leaf-litter spiders and habitat structure as well as the different in species composition between regions have been discussed in the paper.